A new short version of the Posttraumatic Diagnostic Scale: validity among Japanese adults with and without PTSD. Issue 1 (1st January 2017) - Itoh, Mariko; Ujiie, Yuri; Nagae, Nobukazu; Niwa, Madoka; Kamo, Toshiko; Lin, Mingming; Hirohata, Sayuri; Kim, Yoshiharu
ABSTRACT: Background : Identifying high-risk groups for posttraumatic stress disorder (PTSD) during evacuation situations requires a valid short screening tool. The re-experiencing symptoms of PTSD are considered helpful for distinguishing those with PTSD from those without, as they are thought to be specific to PTSD, have less ambiguity for respondents, and are representative of all PTSD symptoms. Objective : To develop a new short version of the Posttraumatic Diagnostic Scale (PDS) comprising only re-experiencing symptom items. Method : We used existing data ( N = 169) from our previous study on the Japanese version of the PDS and the Clinician-Administered PTSD Scale (CAPS). The sample included both clinical outpatients ( n = 106) and university students ( n = 63), all of whom reported one or more traumatic experiences. We created candidate 2- and 3-item versions of the PDS and compared their psychometric characteristics against the CAPS. Results : The best candidate (comprising items for 'intrusive images', 'nightmares', and 'physiological reactions when reminded of the trauma') demonstrated an area under the curve of .95, 94.8% sensitivity, 86.1% specificity for the best cut-off score of three. The candidate scale also showed a strong correlation with CAPS-evaluated severity score and internal consistency. Conclusions : The brief re-experiencing PDS had good psychometric properties among Japanese adults with and without PTSD.